2022
DOI: 10.3389/fphar.2022.971444
|View full text |Cite
|
Sign up to set email alerts
|

Novel perspectives on the therapeutic role of cryptotanshinone in the management of stem cell behaviors for high-incidence diseases

Abstract: Cryptotanshinone (CTS), a diterpenoid quinone, is found mostly in Salvia miltiorrhiza Bunge (S. miltiorrhiza) and plays a crucial role in many cellular processes, such as cell proliferation/self-renewal, differentiation and apoptosis. In particular, CTS’s profound physiological impact on various stem cell populations and their maintenance and fate determination could improve the efficiency and accuracy of stem cell therapy for high-incidence disease. However, as much promise CTS holds, these CTS-mediated proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Cryptotanshinone is a monomer with various pharmacological activities extracted from Salvia miltiorrhiza, which has various effects such as anticancer, anti‐inflammatory, anti‐oxidation, anti‐diabetes and anti‐obesity 233 . Cryptotanshinone comes from natural medicines and has the advantages of low toxicity and wide indications 233–235 . Yan et al.…”
Section: Natural Compounds Targeting Ferroptosis In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptotanshinone is a monomer with various pharmacological activities extracted from Salvia miltiorrhiza, which has various effects such as anticancer, anti‐inflammatory, anti‐oxidation, anti‐diabetes and anti‐obesity 233 . Cryptotanshinone comes from natural medicines and has the advantages of low toxicity and wide indications 233–235 . Yan et al.…”
Section: Natural Compounds Targeting Ferroptosis In Breast Cancermentioning
confidence: 99%
“…233 Cryptotanshinone comes from natural medicines and has the advantages of low toxicity and wide indications. [233][234][235] Yan et al found that cryptotanshinone inhibits tumour growth by promoting ferroptosis in granulocytic myeloid-derived suppressor cells and TNBC cells through proteomics, single-cell transcriptome sequencing, ferroptosis phenotype detection, DARTS, microthermophoresis and molecular docking. 236…”
Section: Cryptotanshinonementioning
confidence: 99%